UMPSA celebrates 100 international graduates from 19 countries at 19th Convocation - Jamilah Bebe, Mohamad (UMPSA, 2024)
GAMBANG, 26 October 2024 – Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) marked a proud milestone by celebrating the achievements of 100 international graduates from 19 countries at its 19th Convocation Ceremony, held from 26 to 29 October 2024 at the Sports Complex Hall, Gambang Campus.